CARM1 (PRMT4) acts as a transcriptional coactivator during retinoic acid-induced embryonic stem cell differentiation - Quintero, Cynthia M.; Laursen, Kristian B.; Mongan, Nigel P.; Luo, Minkui; Gudas, Lorraine J. (Elsevier, 2018)
Activation of the retinoic acid (RA) signaling pathway is important for controlling embryonic stem cell differentiation and development. Modulation of this pathway occurs through the recruitment of different epigenetic regulators at the retinoic acid receptors (RARs) located at retinoic acid responsive elements (RAREs) and/or RA-responsive regions of RA-regulated genes. Coactivator-associated arginine methyltransferase 1 (CARM1, PRMT4) is a protein arginine methyltransferase that also functions as a transcriptional coactivator. Previous studies highlight CARM1’s importance in the differentiation of different cell types. We address CARM1 function during RA-induced differentiation of murine embryonic stem cells (mESCs) using shRNA lentiviral transduction and CRISPR/Cas9 technology to deplete CARM1 in mESCs. We identify CARM1 as a novel transcriptional coactivator required for the RA-associated decrease in Rex1 (Zfp42), and for the RA induction of a subset of RA-regulated genes, including CRABP2 and NR2F1 (Coup-TF1). Furthermore, CARM1 is required for mESCs to differentiate into extraembryonic endoderm in response to RA. We next characterize the epigenetic mechanisms that contribute to RA-induced transcriptional activation of CRABP2 and NR2F1 in mESCs and show for the first time that CARM1 is required for this activation. Collectively, our data demonstrate that CARM1 is required for transcriptional activation of a subset of RA target genes, and we uncover changes in the recruitment of Suz12 and the epigenetic H3K27me3 and H3K27ac marks at gene regulatory regions for CRABP2 and NR2F1 during RA-induced differentiation.